Penetapan Biaya Upah Petani Jagung dalam Konsep Huyula: Studi Kasus di Desa Bukit Aren - Gita Febriani Panigoro, Gita Febriani Panigoro; Mattoasi, Mattoasi; Siti Pratiwi Husain, Siti Pratiwi Husain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research departs from the phenomenon of wage-wage practices that occur in Bukit Aren Village using the local community's traditional system, namely the mutual cooperation system or in Gorontalo language known as